Development of Popular Education in the Podillia Governorate at the Turn of the 19th and 20th Centuries: From Parish Schools to Zemstvo Schools - Zuziak, Tetiana (Pedagogical Discourse, 2024)
The development of education in Ukraine during the 19th century was deeply influenced by the socio-political changes within the Russian Empire, of which Ukraine was a part. This article explores the impact of educational reforms, particularly the reforms of 1803 and 1864, which significantly expanded the network of primary and secondary schools throughout the region. Despite these advancements, many educational institutions continued to operate with outdated curricula, relying on traditional teaching methods, and often suffered from inadequate resources, which hindered the quality of education. Focusing on the Podolia Governorate as a case study, the article analyzes the role of parish schools, which became the primary educational institutions in rural areas. These schools, though widespread, faced numerous challenges, such as a shortage of qualified teachers, insufficient funding, and lack of proper infrastructure and teaching materials. As a result, the effectiveness of these institutions in providing quality education was often limited. The article also examines the emergence of literacy schools in the mid-19th century. Although their scope was limited, these schools played a vital role in promoting basic literacy among the rural population, where formal schools were scarce. Their development was crucial in increasing educational access in remote areas, providing essential skills to the populace. Furthermore, the article addresses the establishment of zemstvo schools following the 1911 reform. These schools were part of a broader movement aimed at decentralizing education and improving its accessibility, particularly in rural regions. Zemstvo schools were an important step towards modernizing the Ukrainian education system and contributed to the formation of a more structured and comprehensive educational framework. By analyzing these stages of educational reform, the article illustrates both the progress and challenges faced by Ukraine’s education system in the 19th century. Despite the numerous obstacles, these reforms laid the groundwork for the future development of modern education in Ukraine, offering valuable insights into the interplay between socio-political changes and educational transformation.